Bio-based graded porous adsorbent as well as preparation method and application thereof
By combining metal salts with bio-based natural polymers such as sodium alginate, a new adsorbent with a graded porous structure is formed, which solves the problems of low adsorption efficiency and high cost in dye wastewater treatment in the prior art, and achieves a variety of High-efficiency adsorption and industrial application potential of organic dyes.
Patent Information
- Application Number
- CN202411359571.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The prior art cannot efficiently remove organic pollutants in dye wastewater, and traditional adsorption materials have problems such as low adsorption efficiency, high cost and complex synthesis.
A bio-based graded porous adsorbent is used, which forms a novel adsorbent with a graded porous structure by combining a metal salt with a bio-based natural polymer such as sodium alginate. The adsorbent is prepared at room temperature in one step, simplifying the traditional multi-step synthesis method and avoiding the use of high temperature and harmful chemicals.
This adsorbent exhibits excellent adsorption properties for a variety of organic dye molecules, especially in removing dyes such as Congo red, which far exceeds the prior art. Its saturation adsorption capacity under neutral conditions reached 1980 mg/g and significantly increased to 4128 mg/g under acid conditions, showing sensitivity and adaptability to pH conditions.
Smart Images

Figure CN119406377A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material science and environmental engineering, and specifically relates to a bio-based hierarchical porous adsorbent and a preparation method and application thereof. Background Art
[0002] In current industrial production, wastewater discharge, especially the discharge of organic pollutants, has caused serious damage to the ecological environment. In particular, in the printing and dyeing, textile and pigment manufacturing industries, the discharge of dye wastewater is particularly prominent. According to statistics, the annual output of dyes in the world exceeds 700,000 tons. Untreated dye wastewater is highly toxic and difficult to degrade, posing a major threat to the ecological environment and human health. Traditional sewage treatment technologies, such as filtration, coagulation and sedimentation, often fail to efficiently remove dye pollutants, and have problems such as low treatment efficiency and long cycle. Therefore, it is particularly important to develop fast, efficient and low-cost printing and dyeing wastewater treatment technology. Adsorption has become one of the widely used printing and dyeing wastewater treatment technologies due to its advantages of economic efficiency, simple operation and no secondary pollution. Activated carbon, polymer materials and metal organic frameworks are common adsorption materials, but they have problems such as low adsorption efficiency, high cost and complex synthesis.
[0003] Metal-organic framework materials (MOFs) have shown potential in the field of water treatment due to their large specific surface area and adjustable pore size, but MOFs in powder form are prone to agglomeration, resulting in reduced adsorption efficiency. For this reason, researchers have begun to pay attention to natural renewable resources, such as chitosan, cellulose, cyclodextrin and sodium alginate, which show application potential in the field of water treatment. Sodium alginate (SA), a polysaccharide derived from natural brown algae, has the advantages of wide sources, simple extraction process and low cost. It contains a large number of carboxyl (-COOH) and hydroxyl (-OH) groups, which can form chelates with multivalent metal ions to prepare biopolymer-based hydrogel adsorbents. However, the dye adsorption capacity of sodium alginate is low and the structural stability needs to be improved.
[0004] Therefore, developing low-cost, green and efficient adsorbents and applying them to printing and dyeing wastewater treatment has become an urgent problem to be solved. Summary of the invention
[0005] The purpose of the present invention is to provide a bio-based hierarchical porous adsorbent and a preparation method and application thereof, wherein the bio-based hierarchical porous adsorbent exhibits excellent adsorption performance for a variety of organic dye molecules.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a bio-based hierarchical porous adsorbent comprises the following steps:
[0008] S1, dissolving a metal salt in a 1-1.5 wt % CaCl2 solution, and ultrasonically treating the solution to obtain a metal salt solution I;
[0009] S2, adding terephthalic acid to deionized water, and then adding solid NaOH to a final concentration of 0.5-1wt%, ultrasonic treatment, and after complete dissolution, adding bio-based natural polymer to a final concentration of 1-1.5wt%, and stirring for 2h to obtain ligand solution II;
[0010] S3. Slowly drip the ligand solution II obtained in step S2 into the metal salt solution I in step S1, allow to stand for aging, collect the precipitate by centrifugation, wash, freeze-dry, and grind to obtain a bio-based hierarchical porous adsorbent.
[0011] Preferably, the metal salt in step S1 is selected from one of Al, Fe, Zr, Ce, Co, Mn metal salts or a mixture of Al-Fe, Fe-Zr, Zr-Ce, Fe-Co metal salts.
[0012] Preferably, the ultrasonic process parameters in step S1 are: ultrasonic frequency is 40 kHz, ultrasonic power is 100 W, ultrasonic time is 5-10 min, and ultrasonic temperature is 25°C.
[0013] Preferably, the ultrasonic process parameters in step S2 are: ultrasonic frequency of 40 kHz, ultrasonic power of 100 W, ultrasonic time of 5-10 min, and ultrasonic temperature of 25°C.
[0014] Preferably, in step S2, the bio-based natural polymer is selected from one of sodium alginate, chitin, chitosan and cellulose.
[0015] Preferably, in step S3, the ligand solution II obtained in step S2 is slowly dripped into the metal salt solution I, left to stand for aging for 15-20 hours, and centrifuged at 10000 rpm for 5-10 minutes.
[0016] Preferably, in step S3, the precipitate collected by centrifugation is washed three times with deionized water and freeze-dried at -50°C for 12-24h.
[0017] The present invention also provides a bio-based hierarchical porous adsorbent prepared by the preparation method as described above.
[0018] The present invention also provides a bio-based hierarchical porous adsorbent prepared by the preparation method or use of the bio-based hierarchical porous adsorbent in wastewater purification.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] The present invention provides a bio-based hierarchical porous adsorbent and a preparation method thereof. By using natural bio-based renewable polymer materials, the present invention can construct a new type of green environmentally friendly adsorbent with a hierarchical porous structure in one step under room temperature water phase conditions. This preparation process simplifies the traditional multi-step synthesis method, avoids the use of harmful chemicals and high temperature conditions, and reduces energy consumption and environmental impact.
[0021] The bio-based hierarchical porous adsorbent prepared by the present invention exhibits excellent adsorption performance for a variety of organic dye molecules, especially in the removal of organic dyes such as Congo red, and its performance far exceeds the existing technology. Under neutral conditions, the saturated adsorption capacity of the adsorbent reaches 1980 mg / g, and under acidic conditions, its adsorption capacity is significantly increased to 4128 mg / g, showing sensitivity and adaptability to pH conditions. The adsorbent of the present invention has important application potential in the treatment of industrial wastewater and dye wastewater.
[0022] The raw materials used in the present invention, such as sodium alginate and metal salts, are not only cheap and easy to obtain, but are also environmentally friendly materials, which enhances the environmental protection characteristics of the present invention. The green and environmentally friendly synthesis conditions and the simplicity and efficiency of the synthesis process provide a solid foundation for the industrial production and commercial application of the present invention.
[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The flowchart of the preparation of the bio-based hierarchical porous adsorbent of the present invention is as follows;
[0025] Figure 2 The SEM images of the adsorbents provided in Example 1 and Comparative Example 1 of the present invention, wherein: Figure 2 (a) is the SA morphology structure of Comparative Example 1 with a scale of 100 μm. Figure 2 (b) is the morphology structure of SA of comparative example 1 with a scale of 10 μm. Figure 2 (c) is the SA@MIL-53(Al) morphology structure of Example 1 with a scale of 400 nm. Figure 2 (d) is the SA@MIL-53(Al) morphology structure of Example 1 with a scale of 200 nm. Figure 2 (e) is the SA@MIL-53(Al) morphology structure of Example 1 with a scale of 1 μm. Figure 2 (f) is the C element distribution diagram of SA@MIL-53(Al) of Example 1, Figure 2 (g) is the O element distribution diagram of SA@MIL-53(Al) of Example 1. Figure 2(h) is the Al element distribution diagram of SA@MIL-53(Al) of Example 1, Figure 2 (i) is the Ca element distribution diagram of SA@MIL-53(Al) of Example 1;
[0026] Figure 3 XRD, FTIR, BET and BJH characterization results of SA@MIL-53(Al), SA and MIL-53(Al) adsorbents provided in Example 1, Comparative Example 1 and Comparative Example 2, wherein: Figure 3 (a) is the XRD spectrum, Figure 3 (b) is the FTIR spectrum. Figure 3 (c) is the BET spectrum. Figure 3 (d) in the figure is the BJH spectrum;
[0027] Figure 4 The performance test results of the SA@MIL-53(Al) adsorbent provided in Example 1 of the present invention are as follows: Figure 4 (a) is the adsorption result of SA@MIL-53(Al) on 5 kinds of dye molecules. Figure 4 (b) shows the variation trend of the adsorption amount of CR by SA@MIL-53(Al) with the contact time; Figure 4 (c) shows the effect of the dosage of SA@MIL-53(Al) on the CR removal efficiency; Figure 4 (d) shows the changes in the adsorption effect of SA@MIL-53(Al) on CR in the pH range of 3-11; Figure 4 (e) is the pHpzc test result of SA@MIL-53(Al). Figure 4 (f) shows the change in the relationship between the adsorption capacity of SA@MIL-53(Al) and the initial dye concentration;
[0028] Figure 5 This is the adsorption isotherm fitting diagram of CR by the SA@MIL-53(Al) adsorbent provided in Example 1 of the present invention, wherein Figure 5 (a) is the nonlinear adsorption isotherm of the SA@MIL-53(Al) Langmuir model. Figure 5 (b) is the nonlinear adsorption isotherm of the SA@MIL-53(Al) Freundlich model; Figure 5 (c) is the nonlinear adsorption isotherm of SA@MIL-53(Al)Temkin model; Figure 5 (d) in the figure is the nonlinear adsorption isotherm of the SA@MIL-53(Al)Redlich-Peterson model. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0030] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0031] In the present invention, unless otherwise specified, other test materials and instruments and equipment are conventional test materials in the art and can be purchased through commercial channels.
[0032] Example 1
[0033] This embodiment provides a bio-based hierarchical porous adsorbent, and the preparation method includes the following steps:
[0034] S1. Dissolve 50 mmol AlCl3 in 50 mL 1 wt% CaCl2 solution, and ultrasonically treat for 5 min at a frequency of 40 kHz, a power of 100 W, and 25°C to obtain a metal salt solution I;
[0035] S2. Add 50 mmol of terephthalic acid to 50 mL of deionized water, and then add solid NaOH to a final concentration of 0.5 wt%. Ultrasonic treatment was performed at a frequency of 40 kHz, a power of 100 W, and 25°C for 5 min. After complete dissolution, solid sodium alginate was added to a final concentration of 1 wt%, and stirring was continued for 2 h to obtain ligand solution II.
[0036] S3. The ligand solution II obtained in step S2 was slowly dripped into the metal salt solution I, and the mixture was allowed to stand for aging for 15 h. The precipitate was collected by centrifugation at 10,000 rpm for 5 min, washed with deionized water for 3 times, freeze-dried at -50°C for 12 h, and ground to obtain the bio-based hierarchical porous adsorbent SA@MIL-53(Al).
[0037] Example 2
[0038] This embodiment provides a bio-based hierarchical porous adsorbent, and the preparation method includes the following steps:
[0039] S1. Dissolve 100 mmol AlCl3 in 100 mL 1.5 wt% CaCl2 solution, and ultrasonically treat for 10 min at a frequency of 40 kHz, a power of 100 W, and 25°C to obtain a metal salt solution I;
[0040] S2, add 100 mmol of terephthalic acid to 100 mL of deionized water, then add solid NaOH to a final concentration of 1 wt%, and ultrasonically treat for 10 min at a frequency of 40 kHz, a power of 100 W, and 25°C. After complete dissolution, add chitosan to a final concentration of 1.5 wt%, and continue stirring for 2 h to obtain ligand solution II;
[0041] S3. Slowly drip the ligand solution II obtained in step S2 into the metal salt solution I, let it stand for aging for 20 hours, collect the precipitate by centrifugation at 10000 rpm for 10 minutes, wash it with deionized water three times, freeze-dry it at -50°C for 24 hours, and grind it to obtain a bio-based hierarchical porous adsorbent.
[0042] Comparative Example 1 This comparative example provides a sodium alginate adsorbent SA, and the preparation method is as follows:
[0043] At room temperature, 50 mL of 1 wt% sodium alginate was slowly dripped into 50 mL of 1 wt% CaCl2 and aged for 18 hours to obtain a white spherical substance. The solid was vacuum filtered and washed several times with deionized water and freeze-dried to obtain sodium alginate adsorbent SA.
[0044] Comparative Example 2 This comparative example provides a MIL-53 (Al) adsorbent, the preparation method is as follows: 50 mmol of AlCl3 · 6H2O) is dissolved in 50 mL of deionized water, and ultrasonicated for 5 min at a frequency of 40 kHz, a power of 100 W, and 25 ° C to obtain a uniform metal salt solution. 50 mmol of H2BDC is added to 50 mL of deionized water, and 100 mmol of NaOH is added, and ultrasonicated for 5 min at a frequency of 40 kHz, a power of 100 W, and 25 ° C to fully dissolve it to obtain a uniform ligand solution. The above ligand solution is slowly dripped into the metal salt solution, stirred for 12 hours, centrifuged at 10000 rpm for 5 minutes, and then the obtained solid is washed with deionized water several times, freeze-dried, and ground to obtain MIL-53 (Al).
[0045] The effects of the adsorbents provided in Example 1 and Comparative Examples 1-2 were verified by the following tests:
[0046] Physical and chemical characterization: 1. The microscopic morphology of the sodium alginate adsorbent provided in Comparative Example 1 and the bio-based hierarchical porous adsorbent SA@MIL-53(Al) provided in Example 1 was characterized by SEM. The results are as follows: Figure 2 .
[0047] Depend on Figure 2 It can be seen that Figure 2 (a) and (b) in the figure are the morphological structures of sodium alginate adsorbents, which are similar to those reported in the literature. Due to the sublimation of ice during the freeze-drying process, a sponge-like structure is formed. Figure 2 (c)- Figure 2As shown in (e), the microscopic morphology of the bio-based hierarchical porous adsorbent SA@MIL-53(Al) provided in Example 1 shows obvious hierarchical porous characteristics. MIL-53(Al) uses SA as an attachment skeleton and grows into a "coral"-like structure. The entire adsorbent contains both the microporous channels of MOF and a large number of macroporous / mesoporous parts. Figure 2 From the element distribution results of (f)-(i) in FIG, it can be seen that C, O, Al, and Ca elements are relatively evenly distributed in the SA@MIL-53(Al) structure, and the content of Al element is richer than that of Ca element.
[0048] 2. The adsorbents provided in Example 1 and Comparative Examples 1-2 were characterized by XRD, FTIR and BET. The results are as follows: Figure 3 .
[0049] The XRD patterns of SA, MIL-53(Al), and SA@MIL-53(Al) are shown in Figure 3 As shown in (a), the XRD spectrum of SA shows an obvious broad peak at 2θ=22°, revealing the amorphous structure of SA. The XRD spectrum of MIL-53(Al) shows characteristic diffraction peaks of the MIL-53(Al) structure at 2θ=17.36°, 25.11°, 27.89°, and 31.70°. The XRD spectrum of SA@MIL-53(Al) shows the characteristic band of SA at around 2θ=22°. At the same time, the characteristic peaks of MIL-53(Al) appear at 2θ=17.34°, 25.14°, 27.87°, and 31.63°, indicating that Al-MOF is successfully loaded on the surface of the SA matrix.
[0050] Fourier transform infrared spectroscopy (FTIR) analysis was performed on different samples. Figure 3 As shown in (b) in the figure. 1600cm -1 and 1510cm -1 、1410cm -1 Corresponding to the asymmetric and symmetric stretching vibrations of the carboxyl group, 1700 cm -1 The left and right sides correspond to uncoordinated carboxylates, indicating that there are free carboxyl groups in the structure, which can produce more hydrogen bonds. -1 and 1130cm -1 The characteristic absorption peak at is Al 3+ The Al-O bond was formed with the ligand, indicating that the metal ion was connected to terephthalic acid through the Al-O coordination bond. -1 The absorption peak nearby corresponds to the absorption peak of water molecules on the adsorbent surface.
[0051] Figure 3As shown in (c), the N2 adsorption / desorption isotherm of SA@MIL-53(Al) is type IV, and the hysteresis loop is type H3. The BET specific surface area of the adsorbent is 22.797 m 2 / g. Figure 3 From (d) in the figure, we can see that the total pore volume is 0.089 cm 3 / g, the most accessible pore size is 11.479nm. A larger pore size is beneficial to reducing mass transfer resistance and providing more effective adsorption sites.
[0052] 3. The performance of the SA@MIL-53(Al) adsorbent provided in Example 1 was tested as follows: an undiluted stock solution (2500 mg L -1 ), a certain amount of IC, MO, CR, RhB and CV dyes were dissolved in distilled water in different glass jars. The stock solution was then diluted to the desired concentration using a beaker for further study. After adsorption, the adsorbent was separated from the reaction solution by centrifugation. Then, a UV-Vis spectrophotometer was used to measure the maximum absorption wavelength (λ) of the dye solution previously determined. max ) and the supernatant was detected. The effects of contact time (0-120min), adsorbent dosage (0.1-1mg / ml), pH (3-11), temperature (25-45℃) and initial pollutant concentration (100-2500mg / L) on the adsorption capacity of SA@MIL-53(Al) were studied. After treatment, the maximum absorption wavelength of each analyte was determined by UV-visible spectrophotometry, and the concentration of the pollutant was calculated. All experiments were repeated twice and the average value was taken for data analysis. The ability of SA@MIL-53(Al) to adsorb pollutants and the percentage of pollutants removed were calculated using equations (1) and (2). The calculation formula is as follows:
[0053]
[0054] Where C0 and C e (mg L -1 ) are the initial concentration and final concentration of the dye solution, respectively; q e (mg g -1 ) is the absorption capacity of the adsorbent at equilibrium; m(g) is the mass of the adsorbent SA@MIL-53(Al); V(L) is the volume of the solution. Figure 4 .
[0055] Depend on Figure 4As shown in (a), the adsorbent SA@MIL-53(Al) has different adsorption effects on five dye molecules, including indigo carmine (IC), crystal violet (CV), Congo red (CR), methyl orange (MO), and rhodamine B (RhB). Among the different dye wastewaters, SA@MIL-53(Al) has the highest adsorption removal rate for Congo red.
[0056] Figure 4 (b) shows the variation trend of the adsorption of CR by SA@MIL-53(Al) with contact time. When the CR concentration is 600 mg / L, more than 70% of the CR adsorbate is adsorbed in the first 20 minutes of the adsorption process. t The value reached 860 mg / g, and then slowly increased until it reached a plateau at 80 minutes. The above results show that SA@MIL-53(Al) has the fastest adsorption rate for CR and has better affinity. As the contact time between the adsorbent / adsorbate increases, the adsorption sites on the surface of SA@MIL-53(Al) are gradually occupied, and the dye molecules begin to diffuse into the internal pores, causing the adsorption rate to slow down until it enters the equilibrium stage.
[0057] exist Figure 4 As shown in (c), the amount of SA@MIL-53(Al) (2-20 mg) has different effects on the CR removal efficiency. In a 600 mg / L CR solution, when only 2 mg of adsorbent is added, the removal rate can reach 80.7%, which shows that SA@MIL-53(Al) is an extremely efficient adsorption material. As the input amount of SA@MIL-53(Al) gradually increases, the removal rate of CR also gradually increases to 93.4%. This is because a higher dose of adsorbent provides sufficient active sites for the removal of CR. When the input amount of SA@MIL-53(Al) increases to 10 mg, the removal rate of CR is close to the maximum value.
[0058] Figure 4 (d) in the figure shows the change in the adsorption effect of adsorbent SA@MIL-53(Al) on CR in the pH range of 3-11. The results show that when the CR concentration is 600 mg / L and pH = 3, SA@MIL-53(Al) can completely remove CR in just 20 minutes. At pH = 5, 7, and 9, SA@MIL-53(Al) can still maintain good adsorption performance and adsorption rate, and has good pH tolerance. However, at pH = 11, the adsorption performance of the adsorbent began to decline. The reason may be that CR is an azo anionic dye containing a negatively charged sulfonic acid group (SO3 - ).
[0059] Depend on Figure 4From (e) in the figure, we can see that the isoelectric point of SA@MIL-53(Al) is 3.5. Therefore, at pH = 3, an electrostatic attraction can be generated between the positively charged adsorbent and CR. As the pH increases, the charge of SA@MIL-53(Al) changes from positive to negative, and the electrostatic attraction between it and CR turns into electrostatic repulsion, causing the adsorption performance to decrease due to electrostatic repulsion. On the other hand, under strong alkaline conditions, there will be many OH- molecules in the solution competing with CR for adsorption sites, resulting in a decrease in the adsorption performance of the adsorbent.
[0060] Figure 4 (f) in Figure 2 shows the relationship between the adsorption capacity of the adsorbent and the initial dye concentration. Under neutral conditions, when the initial concentration of CR is between 100 mg / L and 2000 mg / L, the equilibrium adsorption capacity is significantly enhanced. When the CR concentration is 1500 mg / L, the upward trend begins to slow down, and the maximum adsorption capacity is about 1980 mg / g. At pH = 3, the maximum adsorption capacity of SA@MIL-53(Al) can reach 4128 mg / g, which is about twice that under neutral conditions, indicating that the adsorbent has better adsorption performance at lower pH. Under neutral conditions, due to the presence of a large number of unoccupied adsorption sites on the adsorbent surface, CR molecules can easily interact on the adsorbent surface and quickly reach adsorption equilibrium. Higher dye concentrations will bring greater mass transfer driving force, resulting in an increase in the maximum adsorption capacity. Therefore, with the increase of the initial dye concentration, the adsorption capacity of the adsorbent shows an upward trend. Thereafter, with the further increase of the initial adsorbate CR concentration, the adsorption sites of SA@MIL-53(Al) gradually saturate and reach a relatively stable adsorption platform area.
[0061] 4. The SA@MIL-53(Al) provided in Example 1 was subjected to CR adsorption isotherm fitting, and the experimental scheme was as follows: Adsorption isotherms are often used to describe the relationship between adsorbents and adsorbates under equilibrium conditions.
[0062] The Langmuir, Freundlich, Temkin and Redlich–Peterson models were used to simulate the CR adsorption process. The Langmuir model used to explain the monolayer adsorption is expressed by equation (3); the Freundlich model characterizes the multilayer adsorption in a non-uniform environment, expressed by equation (4); the Temkin model explains the behavior of the solute at the diffusion interface, as shown in equation (5); the Redlich–Peterson model is used to explain the mixed adsorption behavior, as shown in equation (6). This mixed isotherm model has the characteristics of both the Langmuir model and the Freundlich model, and the calculation formula is as follows:
[0063] C e / q e =1 / KL q m +C e / q m
[0064] Formula (3)
[0065] logq e =logK F +1 / n logC e
[0066] Formula (4)
[0067] q e =B T LqCy L +B T LqCy e
[0068] Formula (5)
[0069]
[0070] Where C e (mg / L) is the equilibrium concentration of the dye in the solution, q m (mg / g) is the maximum adsorption capacity. L (L / mg) and K F (mg 1-(1 / n) L 1 / n g -1 ) are the Langmuir and Freundlich model constants, respectively. K T (L / mg) and B T (J.mol -1 ) represent the Temkin constants of maximum equilibrium binding energy and adsorption heat, respectively. K RP is the Redlich-Peterson constant (L·g -1 ), α RP is the binding site affinity (mg -1 ), β is the isotherm index. The nonlinear adsorption isotherms of the four models are shown in Figure 5 The adsorption parameters are shown in Table 1.
[0071] Table 1 Adsorption parameters
[0072]
[0073]
[0074] Depend on Figure 5 It can be seen that the correlation coefficients (R 2) is between 0.92 and 0.96. Compared with other adsorption models, the correlation coefficient (R 2 =0.96) is higher than the correlation coefficient of other model equations, indicating that the adsorption of SA@MIL-53(Al) on CR may be multilayer adsorption. In addition, the n value in the Freundlich model indicates the difficulty of adsorption. Generally, n values less than 0.5 are considered difficult to adsorb, while 2-10 are considered easy to adsorb.
[0075] In Table 1, the n value of SA@MIL-53(Al) is 2.66, indicating that the adsorption process is easy. In addition, the Redlich-Peterson model also has a high correlation (R 2 =0.944), indicating that CR has both physical adsorption and chemical adsorption on the non-uniform surface. In the Temkin model calculation results, the adsorption heat b T The Langmuir fitting results show that the maximum theoretical adsorption capacity of SA@MIL-53(Al) for CR is 2032 mg / g, which is consistent with the actual test results. e The value (1980 mg / g) is relatively close.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a bio-based hierarchical porous adsorbent, characterized in that: The steps include: S1, dissolving a metal salt in a 1-1.5 wt % CaCl2 solution, and ultrasonically treating the solution to obtain a metal salt solution I; S2, adding terephthalic acid to deionized water, and then adding solid NaOH to a final concentration of 0.5-1wt%, ultrasonic treatment, and after complete dissolution, adding bio-based natural polymer to a final concentration of 1-1.5wt%, and stirring for 2h to obtain ligand solution II; S3. Slowly drip the ligand solution II obtained in step S2 into the metal salt solution I in step S1, allow to stand for aging, collect the precipitate by centrifugation, wash, freeze-dry, and grind to obtain a bio-based hierarchical porous adsorbent.
2. The preparation method according to claim 1, characterized in that: In step S1, the metal salt is selected from one of Al, Fe, Zr, Ce, Co, Mn metal salts or a mixture of Al-Fe, Fe-Zr, Zr-Ce, Fe-Co metal salts.
3. The preparation method according to claim 1, characterized in that: The ultrasonic process parameters in step S1 are: ultrasonic frequency of 40 kHz, ultrasonic power of 100 W, ultrasonic time of 5-10 min, and ultrasonic temperature of 25°C.
4. The preparation method according to claim 1, characterized in that: The ultrasonic process parameters in step S2 are: ultrasonic frequency of 40 kHz, ultrasonic power of 100 W, ultrasonic time of 5-10 min, and ultrasonic temperature of 25°C.
5. The preparation method according to claim 1, characterized in that: In step S2, the bio-based natural polymer is selected from one of sodium alginate, chitin, chitosan and cellulose.
6. The preparation method according to claim 1, characterized in that: In step S3, the ligand solution II obtained in step S2 is slowly dripped into the metal salt solution I, left to stand for aging for 15-20 hours, and centrifuged at 10000 rpm for 5-10 minutes.
7. The preparation method according to claim 1, characterized in that: In step S3, the precipitate collected by centrifugation is washed three times with deionized water and freeze-dried at -50°C for 12-24 hours.
8. The bio-based hierarchical porous adsorbent prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the bio-based hierarchical porous adsorbent prepared by the preparation method according to any one of claims 1 to 7 or the bio-based hierarchical porous adsorbent according to claim 8 in wastewater purification.
Citation Information
Patent Citations
Montmorillonite-loaded iron salt MOFs adsorbent and preparation method thereof
CN109663576A
Adsorbent for efficiently removing ciprofloxacin in water and preparation method thereof
CN116272893A
Preparation method and application of bimetallic MOF adsorption composite material
CN117680112A
Preparation method of spherical MOF material
CN118206763A
Synthesis and Application of MOFs / natural Polymers Composite Beads Adsorbents
US20180339284A1